Explaining the premium to NAV in publicly traded Australian REITs, 2008–2018. Issue 1 (17th September 2019) - Erol, Isil; Tyvimaa, Tanja
Abstract : Purpose: The purpose of this paper is to explore the levels and determinants of net asset value (NAV) premiums/discounts for publicly traded Australian Real Estate Investment Trust (A-REIT) market during the last decade. A-REITs were severely affected by the global financial crisis as S&P/ASX 200 A-REIT index-listed property stocks experienced 47 per cent discount to NAV, on average, in 2008–2009 crisis. Since 2013, A-REIT sector has exhibited a strong recovery from the financial crisis and traded at high premiums to date. Understanding the relationship between pricing in the public and private real estate markets has taken on great importance as A-REITs continue to trade at significant premium to NAV unlike their counterparts in the USA and Europe. Design/methodology/approach: This paper follows a rational approach to explain variations in NAV premiums and explores the company-specific factors such as liquidity, financial leverage, size, stock price volatility and portfolio diversification behind the A-REIT NAV premiums/discounts. The study specifies and estimates a model of cross-sectional and time variation in premiums/discounts to NAV using semi-annual data for a sample of 40 A-REITs over the 2008–2018 period. Findings: The results reveal that A-REIT premiums to NAV can be explained not only by the liquidity benefit of listed property stocks but also positive financial leverage effect. During the past decade, A-REITs have followed an aggressive approach in financing their growth by using borrowed funds to purchase assets as the income from the property offsets the cost of borrowing and the risk that accompanies it. Debt-to-equity ratio has to be considered as an important source of NAV premiums as highly geared A-REITs that favoured debt financing over equity financing traded at significant premiums to NAV of their underlying real estate assets. Practical implications: The paper includes implications for the REIT market investors. The regression analysis shows that specialty A-REITs with a focus on creative market niches traded at higher premiums compared with other property stocks, especially in the post-GFC recovery period. Specialty REITs are more highly valued by the market than their traditional specialised counterparts (e.g. office and retail REITs), and those pursuing a diversified strategy. Originality/value: This paper presents an Australian case study as the A-REIT market provides a suitable environment for testing the effect of financial gearing on the REIT premium to NAV. The study provides empirical evidence supporting the importance of debt-to-equity ratio in explaining the variation in A-REIT NAV premiums.